Controlled Leaching Derived Synthesis of Atomically Dispersed/Clustered Gold on Mesoporous Cobalt Oxide for Enhanced Oxygen Evolution Reaction Activity. Issue 9 (6th November 2018) - Youk, Sol; Hwang, Jongkook; Lee, Seonggyu; Kim, Min Su; Lee, Jinwoo
Abstract: The water splitting for hydrogen energy is largely constrained by sluggish anodic oxygen evolution reaction (OER). Cobalt oxide, one of the most promising non‐noble metal catalysts for OER, can exhibit highly enhanced catalytic OER activity when deposited on gold substrates. However, it still remains challenging to develop efficient Au/Co3 O4 catalysts that can maximize the catalytic activity with the minimum use of gold. Here is reported a simple leaching derived synthesis of atomically dispersed/clustered gold on mesoporous cobalt oxides as highly efficient catalysts for OER. With greatly lowered gold contents <1 wt%, the catalyst shows twice as much current density and Au normalized activity than mesoporous cobalt oxide at 400 mV overpotential. The present work provides a simple synthesis route toward atomically dispersed/clustered gold supported catalysts, which can be extended to the development of a wide variety of efficient nanocatalysts that can be designed for specific applications. Abstract : A simple NaCN leaching mediated synthesis of atomically dispersed/clustered Au on mesoporous cobalt oxides (Au/mCo3 O4 ) is provided. With greatly lowered Au contents <1 wt%, the resulting Au/mCo3 O4 shows twice as high current density and Au normalized activity than mCo3 O4 at 400 mV overpotential.